2013
DOI: 10.1093/ajh/hpt129
|View full text |Cite
|
Sign up to set email alerts
|

AT1 Receptors Prevent Salt-Induced Vascular Dysfunction in Isolated Middle Cerebral Arteries of 2 Kidney-1 Clip Hypertensive Rats

Abstract: background Elevated blood pressure, elevated angiotensin II (ANG II), and ANG II suppression with high salt (HS) diet all contribute to vascular dysfunction. This study investigated the interplay of HS diet and vascular function in a high renin model of hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…To the Editor: We recently reported the surprising finding that the salt-induced endothelial dysfunction and downregulation of copper (Cu)/zinc (Zn) superoxide dismutase (SOD) that occurred in cerebral arteries of sham-operated animals were absent in 2 kidney-1 clip (2K1C) hypertensive rats, which exhibit prolonged elevations of plasma angiotensin II (ANG II) levels, and that AT 1 receptor blockade with losartan eliminated endothelium-dependent vasodilation in 2K1C rats. 1 We concluded that the elevated ANG II levels in the 2K1C rats played a key role in protecting against salt-induced vascular dysfunction and suppression of Cu/Zn SOD by upregulating antioxidant defense mechanisms in the arteries.…”
mentioning
confidence: 83%
“…To the Editor: We recently reported the surprising finding that the salt-induced endothelial dysfunction and downregulation of copper (Cu)/zinc (Zn) superoxide dismutase (SOD) that occurred in cerebral arteries of sham-operated animals were absent in 2 kidney-1 clip (2K1C) hypertensive rats, which exhibit prolonged elevations of plasma angiotensin II (ANG II) levels, and that AT 1 receptor blockade with losartan eliminated endothelium-dependent vasodilation in 2K1C rats. 1 We concluded that the elevated ANG II levels in the 2K1C rats played a key role in protecting against salt-induced vascular dysfunction and suppression of Cu/Zn SOD by upregulating antioxidant defense mechanisms in the arteries.…”
mentioning
confidence: 83%
“…При поиске по ключевым словам (NaCl, renovascular hypertension, rats) было найдено в базах 53 публикации (из них 6 обзоров литературы). После исключения статей по заголовкам, резюме, а также повторных публикаций для метаанализа было отобрано 9 публикаций [18][19][20][21][22][23][24][25][26], в которых сравнивалась величина подъема АД после стенозирования почечной артерии у крыс, содержащихся на стандартной диете и высокосолевой диете. В 8 публикациях оценивалось влияние диеты на АРП.…”
Section: влияние диеты с повышенным содержанием Nacl на развитие ургunclassified
“…Angiotensin (Ang) II is known to be one of biological active peptides of RAS, which exerts a fundamental role in sympathetic outflow and cardiovascular activity . The plasma renin, Ang II, and Ang II type 1 receptors (AT1R) in myocardium and ascending aorta are enhanced in animals with hypertensive models . Among a wide range of experimental or genetic models of hypertension, 2K1C hypertensive model is believed to be renovascular Ang II‐dependent hypertension, the transient activation of RAS contributes to the sustained increase in blood pressure …”
Section: Introductionmentioning
confidence: 99%
“…11 The plasma renin, Ang II, and Ang II type 1 receptors (AT1R) in myocardium and ascending aorta are enhanced in animals with hypertensive models. [12][13][14] Among a wide range of experimental or genetic models of hypertension, 2K1C hypertensive model is believed to be renovascular Ang II-dependent hypertension, the transient activation of RAS contributes to the sustained increase in blood pressure. 11,15 Complementary therapies are popular in recent years, and they are considered as promising strategies for the prevention and treatment of cardiovascular disorders including hypertension.…”
mentioning
confidence: 99%